Knowledge of COVID-19 and its prevention among rural residents in Fuqing, China - Xiaojun Liu; Shanshan Du; Ruimei Feng; Lingjun Yan; Yimin Huang; Weimin Ye (Elsevier, 2022)
Objectives: Rural areas are the weakest place for epidemic prevention and control, yet few studies have specifically conducted surveys in rural areas. The purpose of this study is to assess rural residents' knowledge of the COVID-19 and its prevention in China. Methods: A cross-sectional survey study containing 1,426 samples was conducted in Fuqing, China to assess rural residents' knowledge of the COVID-19 and its prevention. Logistic regression was used to identify potential differences in participants' knowledge of COVID-19 and its prevention and control in different population subgroups. Results: The mean and median of residents' knowledge of COVID-19 was 5.53 and 6 points, respectively. The mean and median of residents' knowledge related to self-protection against COVID-19 was 10.34 and 11 points, respectively. Older adults (AOR45-59 = 2.26, 95% CI 1.20 to 4.27; AOR60-69 = 3.13, 95% CI 1.63 to 5.98; AOR≥70 = 4.68, 95% CI 2.35 to 9.33) were more deficient in knowledge of COVID-19. Those who were better educated and with a higher average annual household income were less likely to be deficient in the knowledge of COVID-19 and knowledge of self-protection against COVID-19. Moreover, those who were single, divorced, or widowed (AOR = 1.67, 95% CI 1.13 to 2.46) were more deficient in the knowledge of self-protection against COVID-19. Conclusions: Our study suggests that when facing a pandemic like COVID-19, the key is to inform the public to understand simple and effective self-protection measures. Therefore, we call on the governments to give priority to publicity and education on self-prevention measures for the targeted populations and regions. This is most evident among the vulnerable groups like those who were unmarried, elderly, and those with low education or low income. Similar suggestions may be of use in other countries as well.